Transmural Migration of a Retained Surgical Sponge; A Case Report - Philip, Taah-Amoako; Osei, Ernest; Afua Asieduwaa Bediako-Bowan, Antointette (Journal of Clinical Case Reports and Images, 2026)
Introduction A retained surgical towel in the abdomen is a serious postoperative complication and the most avoidable. Known as “gossypiboma”, it may migrate into adjoining cavities like the stomach, small bowel, colon, vagina, urinary bladder, pericardium, and urethra. Case Report A 32-year-old male presented with complaints of abdominal pain, 4 months after a laparotomy for complicated appendicitis. Initial history and presentation gave an impression of a lower urinary tract obstruction. However, symptoms progressed with signs of bowel obstruction and investigations pointed to a possible retained foreign body. This was confirmed on laparotomy with indications of a transmural migration during the period of evaluation. The report discusses the pathophysiology and manifestations of a migratory surgical gossypiboma. Conclusions A rare case of gossypiboma displaying transmural migration is reported. This showed an initially peritoneally placed sponge that migrated into the intestinal lumen with the sudden presentation of obstructive symptoms. Routine practice of the World Health Organization Surgical Safety Checklist can significantly prevent these incidents.
Keywords: Gossypiboma; surgical towel; transmural migration; ultrasonography; laparotomy